Accumulation of cytoplasmic CDC25A in cutaneous squamous cell carcinoma leads to a dependency on CDC25A for cancer cell survival and tumor growth. (1st December 2017) - Al-Matouq, Jenan; Holmes, Thomas; Hammiller, Brianna; Tran, Nicholas; Holmes, Matti; Freeman, S. Caleb; Hansen, Laura A.
Abstract: Despite its documented role in cell cycle regulation, over-expression of the cyclin-dependent kinase activator CDC25A does not consistently correlate with worse cancer patient outcomes or predict successful clinical response to CDC25A inhibition. The current study was undertaken to investigate CDC25A in skin cancer and understand predictors of positive response to CDC25A targeting. CDC25A was increased in human squamous cell carcinoma (SCC) associated with a shift from a primarily nuclear localization in skin to a strong cytoplasmic localization in SCC, a pattern that was reproduced in skin cancer cell lines. Surprisingly, siRNA-targeting or forced expression of CDC25A failed to alter SCC proliferation. Instead, CDC25A suppressed apoptotic cell death in a manner dependent on both its cytoplasmic localization and interaction with 14-3-3. Normal keratinocytes with nuclear localization of the phosphatase were resistant to CDC25A modulation. Additionally, the CDC25A inhibitors Vitamin K3 or NSC663284 were more toxic to SCC than normal keratinocytes, and CDC25A inhibition effectively suppressed skin cancer growth by increasing apoptosis without affecting normal skin biology. These studies provide proof-of-concept evidence for the potential of CDC25A inhibitors for skin cancer treatment and suggest that an assessment of the cytoplasmic localization of CDC25A may be a strategy for identification of skin and other cancers susceptible to CDC25A targeting.